2019
DOI: 10.1007/s13730-018-0374-6
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosing cholestatic hepatitis in a kidney transplant recipient with hepatitis C virus

Abstract: Fibrosing cholestatic hepatitis (FCH) is a fatal disorder that presents as a progressive deterioration of liver function over a period of several weeks to several months. It is caused by the direct cytotoxic effect of the over-expression of viral antigens on hepatocytes in immunosuppressed patients. Our patient was a 59-year-old man with hepatitis C virus (HCV) infection of genotype 2a who had suffered from end-stage renal disease due to diabetic nephropathy and underwent kidney transplantation. His serum tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Therefore, it is difficult to predict which recipients will develop high levels of early viremia, which may be associated with consequences such as severe hepatitis as we experienced in one recipient, with complete resolution after treatment of HCV. 19,20 In our cohort, none of the other patients developed severe liver-related complications. The majority of our recipients experienced mild to moderate elevations in aminotransferase levels with normal bilirubin levels.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore, it is difficult to predict which recipients will develop high levels of early viremia, which may be associated with consequences such as severe hepatitis as we experienced in one recipient, with complete resolution after treatment of HCV. 19,20 In our cohort, none of the other patients developed severe liver-related complications. The majority of our recipients experienced mild to moderate elevations in aminotransferase levels with normal bilirubin levels.…”
Section: Discussionmentioning
confidence: 62%
“…Unfortunately, UNOS does not routinely report viremia levels for donors. Therefore, it is difficult to predict which recipients will develop high levels of early viremia, which may be associated with consequences such as severe hepatitis as we experienced in one recipient, with complete resolution after treatment of HCV . In our cohort, none of the other patients developed severe liver‐related complications.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, 4 recipients in this study population had concomitant HIV infection. Shinzato et al [ 195 ] reported a case of post renal transplant FCH treated with GLE/PIB combination. The patient expired due to progressive hepatic failure despite decreased HCV viral load.…”
Section: Fibrosing Cholestatic Hepatitis (Fch)mentioning
confidence: 99%
“…К сожалению, у реципиента почки, о котором сообщают авторы из Японии, ФХГ протекал очень быстро и комбинация глекапревира и пибрентасвира к успеху не привела. Пациент умер при явлениях печёночной недостаточности[57]. Несмотря на успехи в эрадикации вируса, которая достигается у большинства реципиентов печени с ФХГ С, фиброз регрессирует только у половины из них.…”
unclassified